Libraries and the need to protect authors´ rights - Pérez-Salmerón, Gloria (Anuario ThinkEPI, 2014)
The position of libraries as society´s guarantors of thefreedom of access to knowledge persists despite barriers to lending digital content, to the collection of digital content in order to preserve it from the "digital black hole" and to the development of digital collections in libraries. The evidence of the lack of minimum international legal standards in a digital environment and in our library sector has raised concerns over the global legal framework that is needed to facilitate the use of digital content in a way that is balanced for both libraries and copyright. The article includes a brief introduction about initiatives by library associations such as IFLA, working together with WIPO to boost TLIB, an international treaty on exceptions and limitations to copyright for libraries, and the EBLIDA campaign, "˜The Right to e-Read´.
Keywords: Libraries; Digital libraries; Copyright; Knowledge; Lending digital content; Digital black hole; EBooks; Digital preservation; Culture heritage preservation; Ifla; Eblida; WIPO; TLIB.